Pemanfaatan Sampah Kaleng Berbahan Plastik Menjadi Furniture Jenis Dingklik - Kristiana Seftianingsih, Dina; Syahnas Paradita, Dea; Rifai, Dian Muhammad (JURNAL KEMADHA, 2023)
Abstract Plastic cans are often produced by toast traders or people who like food that uses bread filled with jam. These plastic cans are usually thrown away or collected and sold to waste collectors. Plastic waste will, of course, take longer to decompose and harm the ecosystem and survival. One way to reduce the impact of plastic can waste is to reuse cans into furnitures with new functions for home furnishings, such as chairs. Plastic cans are short and cannot be formed into chairs of standard sizes. A collection of plastic cans of the same size can be created into a small chair called a "dingklik". Dingklik in Javanese is a small, short chair usually used by mothers who cook in the kitchen. Chairs made from plastic cans can also be used anywhere because the chairs made from the primary material of plastic cans are lightweight with a neater and more aesthetic appearance using supporting materials such as vinyl cloth foam for the seat and hemp rope for covering the can. The results of utilizing plastic cans in valuable chairs are described using a qualitative descriptive design method approach. By utilizing plastic can waste in table products, plastic cans can become a new product that is valuable and can also help reduce the impact of plastic product waste so that environmental sustainability can be well maintained.